2018
DOI: 10.1002/ppul.24064
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor analysis for mortality among infants requiring tracheostomy

Abstract: Among infants with tracheostomy in this cohort, overall mortality rates were relatively low but not insignificant. CHD was associated with increased mortality; however, children with SGS showed more favorable outcomes. Other patient characteristics were not associated with differences in mortality. These data clarify outcomes in a group of infants with tracheostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 32 publications
4
19
0
Order By: Relevance
“…Tracheostomy‐related complications were equally seen in preterm and extremely preterm neonates. Prior studies report mortality rate as low but not insignificant . Strang et al found that in infants ≤12 months of age, the mortality rate was increased in infants requiring tracheostomies with congenital heart disease but was unchanged in infants with BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Tracheostomy‐related complications were equally seen in preterm and extremely preterm neonates. Prior studies report mortality rate as low but not insignificant . Strang et al found that in infants ≤12 months of age, the mortality rate was increased in infants requiring tracheostomies with congenital heart disease but was unchanged in infants with BPD.…”
Section: Discussionmentioning
confidence: 99%
“…12,[15][16][17][18] Additionally, associated morbidities resulting from both the severity of lung disease as well as complications from prolonged exposure to an artificial airway include highly variable but significant rates of neurodevelopmental impairment and structural upper airway disease. [18][19][20][21][22][23][24] Roughly half of the infants born extremely premature develop moderate or severe BPD. 3,4,9 The incidence is rising, indicating that an increasing number of infants will require prolonged ventilatory support, potentially via tracheostomy.…”
Section: Introductionmentioning
confidence: 99%
“…There are few directly comparable studies to examine long‐term mortality rate infant tracheostomy patients given that the majority of studies vary in range of ages included in analysis, tracheotomy indications, and length of follow‐up. Our mortality rate (15.13%) falls within the lower end of the studies on preterm and infant tracheostomy, who cite a mortality rate ranging from 14.2% to 23.53% 4,7,25,26 . However, it remains at upper limit of overall all‐cause mortality rates associated with all ages of pediatric tracheostomy ranging from 1.5% to 18.9% 11,26–30 .…”
Section: Discussionmentioning
confidence: 64%
“…Interestingly, there appears to be a lack of consensus on long‐term outcomes in children with tracheostomy and BPD. Some studies report comparable or decreased rates of mortality among pediatric tracheostomy patients with BPD compared to those without BPD 22,26,31,32 . Other studies report that prematurity and BPD are independent predictors of mortality within this population 33,34 .…”
Section: Discussionmentioning
confidence: 99%